A prova no processo coletivo : teoria dos modelos da prova aplicada ao processo coletivo - Gomes, Camilla de Magalhães (2009)
The essay has the purpose of presenting the model of proof and proof proceeding adapted to Brazilian procedure, more precisely to collective litigation procedure. It is developed from some basic premises, which are the constitutional interpretation of process, the “formalismovalorativo” and the procedural principiology. On the first part, starting from the acknowledgment of the historical and cultural character of Law, it aims to expose the subject of the systems and models of proof. The study of the models of proof shows, in contrast, the classic and modern models of proof and the adequacy of that first to the new methodology of Civil Procedure. The building of the new argumentative-cooperative model demands the recognition of process as a fundamental right and as the center of Civil Procedure science, along with the necessary change of the paradigms of Civil Procedure. From this new model, a new interpretation is searched for the principles and rules of Civil Procedure and, particularly, collective litigation procedure. Therefore, it matters to analyze some of the principles that are characteristic of the class actions micro-system, proving the direct influence of this new outline of thought on the collective litigation procedure. The purpose is to situate the collective actions on this new methodologic phase and to open the way for the following analysis, the one of the rules of proof. With a critic view are analyzed and reformulated the following fundamental issues: a) the organization of procedure and the preliminary hearing as moments of defining and delimitation of the “problem”; b) the alter of the paradigms that involve the petition and its basis; c) the burden of proof, its inversion, distribution and the moment of the decision for both with the corresponding opportunity to produce the evidence; d) the interpretation of the rule of collateral sttopel secundum eventum probationis faced with the methodology and rationality of the micro-system; e) the evaluation of the proof taken on civil investigation and f) possible solutions and innovations brought by the proposals of legislative alter on the issue. Only with the due identification of the Brazilian model of proof and a regime of proof procedure of its own it is be possible to give the correct guidance to the existing legislation and to those ones which intention is to introduce in the system.